Contact dermatitis due to ultrasound gel: A case report and published work review. Issue 3 (8th September 2015) - Chasset, François; Soria, Angèle; Moguelet, Philippe; Mathian, Alexis; Auger, Yvain; Francès, Camille; Barete, Stéphane
Abstract: Adverse skin reactions with ultrasound gel are rare and related mostly to allergic contact dermatitis or contact urticaria. We report an allergic contact dermatitis with Doppler ultrasound gel applied in a 67‐year‐old man. The patient developed atypical purpuric cutaneous presentation located on vascular axes. Semi‐open test with ultrasound gel and patch test with phenoxyethanol were followed by the same clinical purpuric eruption which strongly suggested the accountability of this later component as allergen. Based on this observation, we present a review of published work with a focus on clinical features and allergens involved in ultrasound gel cutaneous reaction.